Penerapan Teori Belajar Kognitif Pada Mata Pelajaran PAI Tingkat SMP di SIT Bina Insan Batang Kuis - Muhammad Alpin Hascan; Suyadi Suyadi (Universitas Muhammadiyah Enrekang, 2021)
Abstract: The theory of learning in the world of education is many in number, one that is often and commonly used especially in Indonesia is the theory of cognitive learning. Cognitive theory is one of the other theories that are quite effective in its application. This study aims to examine the application of cognitive learning theory in PAI subjects at junior high school at Bina Insan Batang Kuis Integrated Islamic School. This study uses a descriptive qualitative approach that is studied through library studies. The results of this study showed that cognitive learning theory is effective to be applied in junior high school SDIT Bina Insan. Such effectiveness must be supported by the creativity of educators by using strategies, methods and media so that cognitive learning theories can be applied in accordance with expectations. Keywords: Theory, Cognitivism, Applications, Learning Abstrak: Teori belajar dalam dunia pendidikan banyak jumlahnya, salah satu yang sering dan lazim digunakan khususnya di Indonesia adalah teori belajar kognitif. Teori tersebut merupakan satu diantara teori-teori lain yang cukup efektif dalam aplikasinya. Penelitian ini bertujuan untuk mengkaji penerapan teori belajar kognitif pada mata pelajaran PAI tingkat SMP di Sekolah Islam Terpadu Bina Insan Batang Kuis. Penenlitian ini menggunakan pendekatan kualitatif deskriptif yang dikaji melalui studi pustaka. Hasil penelitian ini menunjukkan bahwa teori belajar kognitif efektif untuk diterapkan di sekolah SDIT Bina Insan tingkat SMP. Efektivitas tersebut harus didukung dengan kreativitas pendidik dengan menggunakan strategi, metode dan media agar teori belajar kognitif dapat diaplikasikan sesuai dengan harapan. Kata kunci: Teori, Kognitif, Aplikasi, Pembelajaran